1989
DOI: 10.1159/000169581
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Peritoneal Dialysis Solutions: Potential Hazards

Abstract: The ideal components of peritoneal dialysate and their ideal concentrations have yet to be defined. This article reviews the hazards inherent in present solutions and emphasises the dual needs for uniformity of approach to composition and for agreement on minimal international standards for solution quality control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…GDP have been shown, in in vitro studies, to be cytotoxic, to modulate cell proliferation, cell migration, to retard remesothelialization, and to down-regulate cytokine and growth factor synthesis [13,[17][18][19][20]. In vivo studies have highlighted potential adverse effects of GDP on leukocyte recruitment [21,22], and clinical observations have linked GDP to infusion pain and impaired ultrafiltration capacity [23].…”
mentioning
confidence: 99%
“…GDP have been shown, in in vitro studies, to be cytotoxic, to modulate cell proliferation, cell migration, to retard remesothelialization, and to down-regulate cytokine and growth factor synthesis [13,[17][18][19][20]. In vivo studies have highlighted potential adverse effects of GDP on leukocyte recruitment [21,22], and clinical observations have linked GDP to infusion pain and impaired ultrafiltration capacity [23].…”
mentioning
confidence: 99%
“…In addition, the singlet peak corresponded to protons either associated with the S or N (X) atoms, however, the exact identity of the intermediate(s) could not be determined under the conditions of this study. 3 3, were determined. The parameters obtained for the scavenger product and thiazolidine-4-carboxylic acid were identical, confirming that formaldehyde scavenging with L-cysteine produced this derivative.…”
Section: Characterization Of Standard Aminothiol Compoundsmentioning
confidence: 99%
“…Both low and higher molecular weight aldehydes are generated from glucose degradation after the heat sterilization procedure during the manufacture of the solutions. [1][2][3][4][5][6] Aldehydes have also been discovered in freezing solutions, caused by the autoxidation of the cryoprotective compounds. 7 In vitro studies have demonstrated that aldehyde toxicity diminished the viability of frozen mouse oocytes and zygotes; as well as fibroblasts and peritoneal mesothelial cells in culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Neutralizing PD solutions by manually injecting sodium bicarbonate ameliorates such problems; however, this procedure is not practical for treating a large number of patients. 16,17 Neutralizing PD solutions by manually injecting sodium bicarbonate ameliorates such problems; however, this procedure is not practical for treating a large number of patients.…”
Section: Introductionmentioning
confidence: 99%